Legal Analysis of the Regulation of the Minister of Marine Affairs and Fisheries Number 7 of 2024 Concerning Lobster Seed Management from the Perspective of Maslahah Mursalah: A Study of Lobster Seed Export Policy - Tanjung, Nahdila Sapitri; Hidayat, Rahmat (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Minister of Maritime Affairs and Fisheries Regulation Number 7 of 2024, especially Article 18 paragraph (1) which states that supervision of BBL commodities, lobsters (Panulirus spp) crabs (Scylla spp) in fish quarantine installations and/or at entry and/or exit points is carried out by the agency carrying out duties in the field of fish quarantine. This research aims to carry out a juridical analysis of this article and examine its impact from the perspective of maslahah murrasa in Islamic law, which emphasizes maintaining public benefit and preventing loss. This research uses a normative juridical approach in the form of library research, namely researching texts/scripts. The research model used is a bibliographic review of texts/manuscripts of regulations, rules, and policies related to the research theme. The analysis used is content analysis. The results of this research show that the issuance of a ban on the export of lobster seeds aims to preserve lobsters so that they do not become extinct and to improve the welfare of small fishermen in Indonesia. The review of maslahah murlahan is very much in accordance with the study of maslahah murlahan, following the proposition of the Al-Qur'an surah al-An 'am verse: 108, and is reinforced by the fiqh rule